MHD free convective heat and mass transfer flow from a vertical porous surface with variable thermal conductivity, variable mass diffusivity and thermal diffusion including viscous dissipation and chemical reaction - Phakirappa, J.; Priyanka, S.; Veena, P.H.; Pravin, V.K. (Zielona Góra: Uniwersytet Zielonogórski)
An analysis is carried out to study chemically reactive, viscous dissipative effects of an incompressible and electrically conducting fluid with MHD free convection adjacent to a vertical surface with variable thermal conductivity (VTD) and variable mass diffusivity (VMD).
Keywords: MHD; VTD; VMD; viscous dissipation and chemical reaction